2015
DOI: 10.1002/14651858.cd006731.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical policies: effects of financial incentives for prescribers

Abstract: Although financial incentives are considered an important element in strategies to change prescribing patterns, limited evidence of their effects can be found. Effects of policies, including pay for performance policies, in improving quality of care and health outcomes remain uncertain. Because pharmaceutical policies have uncertain effects, and because they might cause harm as well as benefit, proper evaluation of these policies is needed. Future studies should consider the impact of these policies on health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 140 publications
2
41
0
1
Order By: Relevance
“…A meta‐analysis conducted for Cochrane found, based on data from 25 randomized controlled trials, that academic detailing improves compliance with desired prescribing practices . Financial incentives aimed at improving rates of generic prescribing were also shown to be effective, although the evidence base is limited …”
Section: Resultsmentioning
confidence: 99%
“…A meta‐analysis conducted for Cochrane found, based on data from 25 randomized controlled trials, that academic detailing improves compliance with desired prescribing practices . Financial incentives aimed at improving rates of generic prescribing were also shown to be effective, although the evidence base is limited …”
Section: Resultsmentioning
confidence: 99%
“…The present study suggests that at least some of the effect observed by Yip et al was because of the P4P component of the new payment scheme. Second, our study contributes to the small literature undertaking rigorous evaluations of the effects of P4P schemes targeting pharmaceutical use and spending, which, according to Rashidian et al (2015), amounted to just three inconclusive studies to date prior to our study and that of Yip et al Finally, our study contributes to the small but growing literature providing rigorous evaluations of P4P schemes in developing countries. Since Witter et al (2012), several new studies have been undertaken, some of which are prospective experiments and others of which are retrospective evaluations of at-scale schemes (Basinga et al, 2011;Wang et al, 2011;Bonfrer et al, 2014a;Bonfrer et al, 2014b;Celhay et al, 2015;de Walque et al, 2015;Van de Poel et al, 2015).…”
mentioning
confidence: 79%
“…22 Insentif finansial juga dianggap sebagai elemen penting dalam mengubah pola resep dokter walaupun dampak kebijakan seperti sistem pay for performance dalam meningkatkan kualitas hasil perawatan dan kesehatan masih belum pasti sehingga perlu penelitian lebih lanjut. 23 Sama halnya pada dokter pelayanan primer, metode pembayaran berpengaruh pada perilaku pelayanan dokter. Dengan metode pembayaran fee for services berdampak lebih banyak kunjungan ke dokter/dokter spesialis dan layanan diagnostik dibandingkan dengan metode pembayaran kapitasi sehingga perubahan dalam pembayaran insentif finansial dapat meningkatkan kualitas pelayanan di pelayanan primer.…”
Section: Pembahasanunclassified